ANALYSIS OF FACTORS AFFECTING THE IMPLEMENTATION OF SOCIAL AND ENVIRONMENTAL RESPONSIBILITY DISCLOSURE IN PROPERTY, REAL ESTATE, AND CONSTRUCTION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2015-2020 - Kurniawati, Lintang; kholis, Nur; Mujiyati, M (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to determine the analysis of the factors that influence the implementation of corporate social and environmental responsibility disclosures in property, real estate, and construction sector companies listed on the Indonesia Stock Exchange in 2015- 2020. The first step of this research is to prepare a framework for the research to be made, and collect data from www.idx.go.id by downloading the annual report of the sampled company following the sample criteria and variables required in the study. The sample obtained from this study is 129 samples and the data is processed using SPSS 21. The results of this study indicate that the factors that influence Corporate Social Responsibility in property, real estate, and construction sector companies are variable size, and managerial ownership. While the variables Leverage, Growth, and the size of the board of commissioners have no effect.